137k views
4 votes
HELP!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!

HELP!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!-example-1
User Jossue
by
5.9k points

2 Answers

1 vote

We have that 114° + y is equal to 180°, so,

114° + y = 180°

y = 180° - 114°

y = 66°

And since every triangle has the sum of 180° in the three angles we can say that

66° + 2x + x = 180°

3x = 180° - 66°

3x = 114°

x = 114°/3

x = 38°

User Boh
by
5.0k points
3 votes

Answer:

A. 38

Explanation:

180- 114 = 66

66 + 2x + x = 180

66 + 3x = 180

-66 -66

3x = 114

— —-

3 3

x = 38

User Sarat Patel
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.